2004
DOI: 10.1080/1355785042000250085
|View full text |Cite
|
Sign up to set email alerts
|

Categorical Ethnicity and Mental Health Literacy in New Zealand

Abstract: Contrary to the embedded assumption within New Zealand's public health strategies that there are essential differences between the way Maori and non-Maori view health problems, and that the categorical ethnicity demarcation reliably reflects these differences, we found no evidence for the veracity of this claim using a major depressive disorder as a target for judgements. Alternative explanations are canvassed as to why this assumption about fundamental differences based on categorical ethnicity has gained asc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…A more complex approach to understanding the role of community-based culture and their influence on health and health care is essential to the understanding of unmet need, delay, and low utilization rates that trouble providers and policymakers. As Marie et al (2004) conclude in New Zealand, the “assumed” relationship between “categorical ethnicity” (e.g., in their case, Maori/non-Maori) and mental health literacy that undergirds public social policies appear to be fundamentally misdirected. For major depression, most majority and minority-identified individuals in their study could correctly identify the “disorder” from a vignette.…”
Section: Discussionmentioning
confidence: 98%
“…A more complex approach to understanding the role of community-based culture and their influence on health and health care is essential to the understanding of unmet need, delay, and low utilization rates that trouble providers and policymakers. As Marie et al (2004) conclude in New Zealand, the “assumed” relationship between “categorical ethnicity” (e.g., in their case, Maori/non-Maori) and mental health literacy that undergirds public social policies appear to be fundamentally misdirected. For major depression, most majority and minority-identified individuals in their study could correctly identify the “disorder” from a vignette.…”
Section: Discussionmentioning
confidence: 98%
“…For example, Parker et al. [14] reported ‘more similarities than differences’ between health professionals in Australia and Singapore, and Marie, Forsyth and Miles [15] found little variation between Maori and non‐Maori identification of depression and associated treatment beliefs. Despite this, the current findings indicated that it is unlikely that the instruments currently used to measure mental health literacy are sufficiently sensitive to capture perceptions of mental health across all cultural groups, nor bridge language barriers.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 162 papers containing relevant information could be identified. If necessary, native speakers were contacted to provide translations.…”
Section: Methodsmentioning
confidence: 99%